2017
DOI: 10.3892/ol.2017.7669
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAT2 promotes epithelial-mesenchymal transition involving Wnt/β-catenin pathway in epithelial ovarian carcinoma cells

Abstract: Abstract. Long non-coding RNA colon cancer-associated transcript 2 (CCAT2) is dysregulated in a variety of types of human cancer. However, the role of CCAT2 in epithelial ovarian carcinoma (EOC) remains largely unknown. The aim of this study is to investigate the effect of CCAT2 on epithelial-mesenchymal transition (EMT) and related molecular mechanisms in epithelial ovarian cancer cells. In the current paper, we found that CCAT2 was significantly upregulated in EOC SKOV3, A2780 and HO8910 cell lines compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…These results confirm a previous investigation wherein CCAT2 was shown to regulate the migration and invasion of cholangiocarcinoma cells [19]. In another study lncRNA was reported to exert its effects via regulation of the wnt/β-catenin signaling pathway in epithelial ovarian cancer cells [20]. The results showed that CCAT2 suppression also inhibits the wnt/β-catenin pathway in OVACAR-3 cells.…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm a previous investigation wherein CCAT2 was shown to regulate the migration and invasion of cholangiocarcinoma cells [19]. In another study lncRNA was reported to exert its effects via regulation of the wnt/β-catenin signaling pathway in epithelial ovarian cancer cells [20]. The results showed that CCAT2 suppression also inhibits the wnt/β-catenin pathway in OVACAR-3 cells.…”
Section: Discussionsupporting
confidence: 90%
“…[30][31][32] We suspected that the autophagy may be activated in GC cells to protect against apoptosis. The action mechanisms of CCAT2 on tumors are complex, which involve diverse regulatory factors, such as E-cadherin/LATS2, 10 P15, 33 GSK3β/β-catenin, 34 Wnt/ β-catenin, 35 and TGF-β. 21 In this study, the specific regulatory relationship between CCAT2 and mTOR signaling was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, CCAT2 has been certified as an oncogene in other neoplasms. [31][32][33] In particular, suppression of in-vitro CCAT2 expression was able to hinder both proliferation and invasion of breast cancer cells, and tumor growth in animal models was also restrained by lowly expressed CCAT2. 34 Moreover, dysfunctional CCAT2, due to mutation of alleles in rs6983267, also boosted aggravation of colorectal cancer through affecting Wnt signaling, 35 but whether SNP rs6983267 also played an analogous part underlying glioma pathogenesis was unknown.…”
Section: Discussionmentioning
confidence: 99%